The Debilitating State of the Maiduguri Main Abattoir, Poor Sanitary and Waste Disposal Methods; the Way Forward (2016)
An abattoir provides facilities where animals are slaughtered. The current state of most abattoirs in developing countries particularly Nigeria are a matter of concern considering the enormous lapses in their operations, the sanitary conditions and management. The northern part of Nigeria is the worst hit since the majority of food animals are domiciled in the region. This study was aimed at determining the state of facilities, sanitary conditions and practices of abattoir workers and the veterinary doctors in a major abattoir in North-eastern Nigeria. This observational study was carried out over a period of three months in the main abattoir in Maiduguri, northeastern Nigeria. During the period, we documented the states of the facilities in the abattoir, the sanitary conditions as well as the practices of abattoir workers and the veterinary doctors present. Our findings revealed that the lairage was in a poor state and the drainages were clogged with debris and maggots. There were no meat stands and cold room and the entire surrounding environment was full of stench emanating from poorly disposed abattoir wastes. Besides, both ante-mortem and post-mortem inspections were hardly carried out and animals were being slaughtered in the open with carcasses processed on bare floor. Dragging of viscera’s on the floor and washing of the stomachs in the drainages in addition to slaughtering of calves and pregnant animals were common practices observed at the abattoir. We documented the poor states of facilities, sanitary conditions and practices in the main abattoir in northeastern Nigeria. Our findings suggest a compromise in the quality of meat being produced from the abattoir with overall devastating effects on the health of meat consumers. While quality meat production is key to achieving a healthy society, there is a need for a synergy among all the stakeholders particularly the government and private organizations towards improving the state of abattoirs in Nigeria with respect to the facilities, sanitary conditions and practices.